PELATIHAN TEKNIS JURNALISTIK BAGI ANGGOTA IATCA – INDONESIAN AIR TRAFFIC CONTROLLER ASSOCIATION - A. Rahman, A. Rahman (Universitas Esa Unggul, 2018)
AbstractThis community service activity aims to help realize the elevation of the DPP IATCA (Indonesia Air Traffic Controller Association) so that its members have the ability to have good relations with journalists and are able to manage the media belonging to the organization. The training was held for two full days so that they could provide knowledge, understanding, and skills in the field of journalism and how to deal with modern mass media. Submission of material is carried out by striving to open up opportunities for participants to discuss comprehensively and carry out the practice under the guidance of the trainer. As a result, the trainees were able to manage the new media belonging to the organization, namely